# Elementary differential equations 7th edition - Boyce W.E

ISBN 0-471-31999-6

**Download**(direct link)

**:**

**337**> 338 339 340 341 342 343 .. 486 >> Next

c^3+ c2t! = 0. These equations have a nontrivial solution for c1 and c2 only if the determinant of coefficients is

zero. But the determinant of coefficients is -2t^t1 n 0 for t0 and t1 as specified. Hence f(t) and g(t) are linearly independent on -1 < t < 1.

Section 3.4, Page 158 1. exp(1+2i) = e1+21= ee21 = e(cos2 + isin2).

5. Recall that 21_i = eln(21-1) = e(1-i)ln2

rt

7. As in Section 3.1, we seek solutions of the form y = e . Substituting this into the D.E. yields the characteristic 2

equation r - 2r + 2 = 0, which has the roots r1 = 1 + i

44

Section 3 . 4

11.

14.

18.

22.

23a.

and r2 = 1 - i, using the quadratic formula. Thus l = 1 and m = 1 and from Eq.(17) the general solution is y = c1etcost + c2efcsint.

2

The characteristic equation is r + 6r + 13 = 0, which

-6+v-16

has the roots r =

-3±2i. Thus l = -3 and

m = 2, so Eq.(17) becomes y = c1e 3tcos2t + c2e 3tsin2t.

The characteristic equation is 9r + 9r - 4, which has the real roots -4/3 and 1/3. Thus the solution has the

same form as in Section 3.1, y(t) = c1et/3 + c2e-4t/3.

The characteristic equation is

r + 4r + 5 = 0, which has the roots r1,r2

-2t

-2 ± i. Thus

2t

'cost + c2e

sint and

-2t

cost +

y = c1e

y' = (-2c1+c2)e

-2t

(-c1-2c2)e sint, so that y(0)= c1= 1 and y'(0) = -2c1+c2= 0,

2t

or c2 = 2.

Hence y = e

cost + 2sint)

o.a 04 o§ 0.8 (*ia i.^ij 22I14 sb as 3

The characteristic equation is

2

r + 2r + 2 = 0, so r1,r2 = -1 ± i.

Since the I.C. are given at p/4 we want to alter Eq.(17) by

^p/4

d1 and c2

letting c1

Thus, for l = -1 and m = 1 we

e-(t-p/4)

-(t-p/4)

P/4,

ed

have y = e (t p/4) (d1cost + d2sint)

? (t-P/4)

so y = -e (d1cost + d2sint) +e (-d1sint +d2cost)

Thus ^/2d1/2 + \J~2d2/2 = 2 and -^/"2d1 = -2 and hence y = \f2 e (t p/4) (cost + sint).

The characteristic equation is 3r

1 . a/23 .

the roots r1,r2 = ±

i.

6

t/6 ( V23

e (c.cos----

16

t + c2sin

6

2 r + 2 Thus u(t) =

0, which has

6

t) and we obtain u(0) = c1 = 2

2

Section 3.4

45

, 1 /23"

and u (0) = c + c2 = 0. Solving for c2 we find

6 1 6 2 2

t/s 323 2 323

u(t) = e / (2cos 1 - sin 1).

6 y23 6

23b. To estimate the first time that | u(t) | = 10 plot the graph of u(t) as found in part (a). Use this estimate in an appropriate computer software program to find t = 10.7598.

2

25a.The characteristic equation is r + 2r + 6 = 0, so

r1,r2 = -1 ± ^J~5i and y(t) = e-t(c1cosV~51 + c2sin33t).

Thus y(0) = c1 = 2 and y'(0) = -c1 + \/~5 c2 = a and hence

-t / a+2 1

y(t) = e (2cosy 5 t + sin y5t).

-1 / a+2 I

25b. y(1) = e (2cosy5 + ,__ sin y 5 ) = 0 and hence

V 5

2y 5

a = -2 - ---------- = 1.50878.

tanV 5

t a+2 t

25c. For y(t) = 0 we must have 2cosy5t +__________________ siny5t = 0 or

V 5

I -2 V 5

tany 5 t = --------. For the given a (actually, for a > -2)

a+2

I 2 y 5

this yields V 5 t = p - arctan since arctan x < 0 when

a+2

x < 0.

2\f~5

2 5d. From part (c) arctan ---------- 0 as a ? , so t ? p

a+2

31. -d[e1t(cosmt + isinmt)] = 1e1t(cosmt + isinmt) dt

+ e1t(-msinmt + imcosmt) = ie1t(cosmt + isinmt)

+ ime1t(isinmt + cosmt) = e1t(i+im) (cosmt + isinmt).

_ rt rt

Setting r = l+im we then have e = re .

dt

33. Suppose that t = a and t = b (b>a) are consecutive zeros of y1. We must show that y2 vanishes once and only once in the interval a < t < b. Assume that it does not

46

Section 3 . 4

35.

38.

vanish. Then we can form the quotient y1/y2 on the

interval a < t < b. Note y2(a) n 0 and y2(b) n 0,

otherwise y1 and y2 would not be linearly independent

solutions. Next, y1/y2 vanishes at t = a and t = b and

has a derivative in a < t < b. By Rolles theorem, the derivative must vanish at an interior point. But

yi y1y2 - y2yi -W(yi,y2)

( )' = ----------- = , which cannot be zero

y 2 2 y2 y2 y2

since y1 and y2 are linearly independent solutions.

Hence we have a contradiction, and we conclude that y2 must vanish at a point between a and b. Finally, we show that it can vanish at only one point between a and b. Suppose that it vanishes at two points c and d between a and b. By the argument we have just given we can show that y1 must vanish between c and d. But this contradicts

the hypothesis that a and b are consecutive zeros of y1.

-t2

We use the result of Problem 34. Note that q(t) = e > 0 for - < t < . Next, we find that (q' + 2pq)/q3/2 = 0. Hence the D.E. can be transformed into an equation with

r -t2/2

constant coefficients by letting x = u(t) = J e dt. Substituting x = u(t) in the differential equation found in part (b) of Problem 34 we obtain, after dividing by the

2 2 2 2 coefficient of d y/dx , the D.E. d y/dx - y = 0. Hence the

general solution of the original D.E. is y = c1cosx + c2sinx,

f -t2/2 = J e dt.

Rewrite the D.E. as y" + (a/t)y' + (b/t2)y = 0 so that p = a/t and q = b/t2, which satisfy the conditions of parts (c) and (d) of Problem 34. Thus 2 1/2

x = J(1/t ) ' dt = lnt will transform the D.E. into

dy2/dx2 + (a-1)dy/dx + by = 0. Note that since b is constant, it can be neglected in defining x.

**337**> 338 339 340 341 342 343 .. 486 >> Next